Effect of Intravenous Thrombolysis Prior to Mechanical Thrombectomy According to the Location of M1 Occlusion - Jae-Chan Ryu; Boseong Kwon; Yunsun Song; Deok Hee Lee; Jun Young Chang; Dong-Wha Kang; Sun U. Kwon; Jong S. Kim; Bum Joon Kim (Journal of Stroke, 2024)
Background and Purpose The additive effects of intravenous thrombolysis (IVT) before mechanical thrombectomy (MT) remain unclear. We aimed to investigate the efficacy and safety of IVT prior to MT depending on the location of M1 occlusion. Methods We reviewed the cases of patients who underwent MT for emergent large-vessel occlusion of the M1 segment. Baseline characteristics as well as clinical and periprocedural variables were compared according to the location of M1 occlusion (i.e., proximal and distal M1 occlusion). The main outcome was the achievement of functional independence (modified Rankin Scale score, 0–2) at 3 months after stroke. The main outcomes were compared between the proximal and distal groups based on the use of IVT before MT. Results Among 271 patients (proximal occlusion, 44.6%; distal occlusion, 55.4%), 33.9% (41/121) with proximal occlusion and 24.7% (37/150) with distal occlusion underwent IVT prior to MT. Large-artery atherosclerosis was more common in patients with proximal M1 occlusion; cardioembolism was more common in those with distal M1 occlusion. In patients with proximal M1 occlusion, there was no association between IVT before MT and functional independence. In contrast, there was a significant association between the use of IVT prior to MT (odds ratio=5.30, 95% confidence interval=1.56–18.05, P=0.007) and functional independence in patients with distal M1 occlusion. Conclusion IVT before MT was associated with improved functional outcomes in patients with M1 occlusion, especially in those with distal M1 occlusion but not in those with proximal M1 occlusion.